1970
DOI: 10.1021/bi00819a002
|View full text |Cite
|
Sign up to set email alerts
|

Studies of self-association and conformation of peptides by thin-film dialysis

Abstract: The tyrocidine antibiotic polypeptides are known to exhibit self-association. They were therefore used as test substances to document the behavior to be expected by the method of thin-film dialysis. Self-association with these peptides is indicated by concentration dependence, a reverse curvature of the escape plot, and a retardation of the rate of diffusion by addition of salt but an acceleration by the addition of ethanol or other hydrophobic bond breaking solvent additives. A survey of dipeptides by thin-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1973
1973
2002
2002

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
(16 reference statements)
1
7
0
Order By: Relevance
“…tides, recently reported by BURACHIK et al 1) it is shown in this paper that the half-escape times are linearly related to the cube root of the molecular weights of the peptides. The slopes of the two lines defined respectively by the alanine and the glycine peptides differ s m c a n t l y , and the fact that data points obtained for various composite dipeptides and for the alanine amino acid fall on the line defined by the glycine peptides indicates an exceptional diffusion behavior of the alanine peptides.…”
supporting
confidence: 60%
See 3 more Smart Citations
“…tides, recently reported by BURACHIK et al 1) it is shown in this paper that the half-escape times are linearly related to the cube root of the molecular weights of the peptides. The slopes of the two lines defined respectively by the alanine and the glycine peptides differ s m c a n t l y , and the fact that data points obtained for various composite dipeptides and for the alanine amino acid fall on the line defined by the glycine peptides indicates an exceptional diffusion behavior of the alanine peptides.…”
supporting
confidence: 60%
“…It may be added that it was evident already from one of the correlations suggested by BURACHIK et al 1) that the alanine amino acid could not be easily aligned with the alanine peptides (Fig. With 2 R as the diffusional diameter the equation would define a linear relation between diffusion rates and the cube root of the molec-Thin-Film Dialysis Rates of Peptides ular weight for the molecules in question But the equation cannot be applied to the results of BURACHIK et al 1) without qualifications, among which the most serious may be t h a t it is expected not t o hold for solute molecules with a molecular weight less than about 1000. That the test points for the longest axes could not be fitted to a straight line was in fact due t o the point arising from measurements on the amino acid.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Therefore it is unexpected that the E values of triglycine and tetraglycine are so similar. According to Craig et al [16] polyglycine chains must be more flexible than other polypeptides because of the absence of side chains and strong steric hindrance and, on the basis of spectroscopic data, Destrade et al [17] proposed a torsional conformation stabilized by intramolecular hydrogen bonds for diglycine and triglycine in water. It may therefore be supposed that our two peptides tend to adopt a spherical shape, reducing the contact surface with the surrounding water molecules.…”
Section: Discussionmentioning
confidence: 99%